2016
DOI: 10.1016/j.nmd.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical delay components during skeletal muscle contraction and relaxation in patients with myotonic dystrophy type 1

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights Patients with myotonic dystrophy type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 35 publications
1
28
1
4
Order By: Relevance
“…In the present study, we found acceptable CV and poor-tohigh ICC (Atkinson & Nevill, 1998). Although lower CV and higher ICC for EMD were previously observed during voluntary contractions (Hopkins et al, 2007;Esposito et al, 2016), studies that have assessed EMD during a simple RT task are scarce, more or less recent (Krall, 1973;Klimovitch, 1977;Stull & Kearney, 1978) and/or did not use electrode array (P€ a€ asuke et al, 1999). It has been proposed that, for longer RT measured in various tasks, the delayed onset of physical processes regulated by white and grey matter initiated later in time, thus explaining the RT variability (Yarkoni et al, 2009).…”
Section: Discussionsupporting
confidence: 63%
“…In the present study, we found acceptable CV and poor-tohigh ICC (Atkinson & Nevill, 1998). Although lower CV and higher ICC for EMD were previously observed during voluntary contractions (Hopkins et al, 2007;Esposito et al, 2016), studies that have assessed EMD during a simple RT task are scarce, more or less recent (Krall, 1973;Klimovitch, 1977;Stull & Kearney, 1978) and/or did not use electrode array (P€ a€ asuke et al, 1999). It has been proposed that, for longer RT measured in various tasks, the delayed onset of physical processes regulated by white and grey matter initiated later in time, thus explaining the RT variability (Yarkoni et al, 2009).…”
Section: Discussionsupporting
confidence: 63%
“…Yet, the time of electric activity anticipates the time of detectable force because of the time needed for impulse conduction, excitation–contraction coupling, alignment of pennate fibers with the tendon, and stiffening of the series elastic elements ( Nordez et al , 2009 ), so that the overall electromechanical delay for force onset was presumably around 50–80 ms in this study. The delay is known to be higher for contraction than for relaxation ( Esposito et al , 2016 ). Also, as a rule, the sEMG signal decreased monotonically from just before to just after the time of detectable positive power (Figs 2 – 4 ), so that the missed sEMG was of non-negligible amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐three unrelated participants with no myotonia, muscle weakness, or clinical history of DM1 were included in the study as presymptomatic candidates. In addition to being DM1 mutation carriers, presymptomatic participants met the following criteria: (1) absence of distal weakness measured according to the Muscular Impairment Rating Scale and by hand‐held dynamometry using reference values adjusted for age and sex (28.46 ± 7.17 and 23.95 ± 6.26 for right and left hands, respectively) and (2) lack of myotonic discharges according to needle examination of cervical paraspinal, trapezius, deltoid, biceps, wrist extensor, first dorsal interosseous, tibialis anterior, and vastus lateralis muscles (Nicolet Viasys Viking Select, Madison, Wisconsin) . Participants with another neuromuscular or neurodegenerative disease, stroke, traumatic brain injury, head and neck cancer, or dystonia were excluded.…”
Section: Methodsmentioning
confidence: 99%